An efficient algorithm for resource optimization in TWDM passive optical network using a C-RAN - Tiang, Jun Jiat; Chung, Hee Chan; Choi, Jaeyoung; Khan, Imran; Alshehri, Asma; Wang, Pi-Chung; Hameed, Ibrahim A. (Frontiers in Physics, 2024)
The traditional base station in C-RAN is divided into three parts: a pool of centralized baseband units (BBUs), a fronthaul network that links the BBU and RRUs, and remote radio units (RRUs). This paper proposes a novel cooperative algorithm for resource optimization in time-wavelength division multiplexed (TWDM) passive optical network (PON) incorporating cloud radio access network (C-RAN). First, a joint collaborative strategy is deployed to optimize the cooperative caching and transmission in wireless and optical domain. Then, the quality-of-experience (QoE) is improved by bandwidth configuration and caching. Simulation results show that the average throughput of the proposed QACCTM algorithm is about 30% higher than that of other algorithms. Compared with the RARCP algorithm and QAWEC algorithm, the proposed QACCTM algorithm reduces the access delay by about 27.1% and 15.9%.